‘Actions of the Eyes of the Fleeing’? Reflections on the In/Visibility of Harraga Videos (Cinéma & Cie. Film and Media Studies Journal, 2017)
Against the backdrop of the media practices of the ‘summer of migration’ in 2015, this article asks if and how cell phone videos recorded by migrants and refugees and circulated via social media channels have not only the capability to change and extend modes of representation. It analyses harraga videos — short cell phone clips of the clandestine passage across the Mediterranean, uploaded on YouTube — by focusing on the act of capture. With reference to Helen Grace and Rey Chow, the essay argues that despite the relative invisibility of the videos, they are not just simple documents, but rather constitute the present of the harraga, and thereby form (local) publics. In this light, they can be understood as a political (media) practice, which intervenes in the visibilities and visualizations of the necropolitical European border regime.